Mutation of CCR5 Delta 32 in Umbilical Cord Blood Samples: Future Potential for HIV-1 Cure - Vinayak Virupaksh Kedage; Satyen Yash Sanghavi; Tripti U Gaunkar; Ravi Kumar Bonthala (Journal of Clinical and Diagnostic Research, 2020)
Introduction: Human Immune Deficiency (HIV) virus is a highly mutagenic virus with diverse antigenic types and subtypes. Long latency leading to persistence in infected cell as provirus which poses great problem in developing HIV cure. The C-C Chemokine Receptor Type 5 (CCR5) molecule is a chemokine receptor, is the most important co-receptor for macrophage-tropic HIV-1 viral entry into the immune cells. In individuals with homozygous 32-bp deletion in the CCR5 gene (CCR5-del32) leads to near-complete resistance to HIV-1 infection, and also improves the prognosis in heterozygous adults with HIV-AIDS by slowing down the progression rate. Aim: Identification of CCR5 genotype in cord blood units of Indian population to generate an effective database, which may be useful as a future potential for treatment of HIV-1. Materials and Methods: This cross-sectional study for CCR5 genotyping was carried out on randomly selected Umbilical cord blood samples over a period of six months from June 2019 to November 2019 at Regrow Biosciences Private Limited, Lonavala, Pune, Maharashtra, India. Cord blood samples were screened for CCR5-del32 mutation by gene amplification using PCR based method from genomic DNA followed by agarose gel electrophoresis. All positive samples were confirmed by capillary electrophoresis. Statistical analysis was calculated using Fisher’s formula. Confidence level was determined at 95% with Confidence interval of 3.46. Results: Out of 800 samples analysed, 21 were found positive for heterozygous genotype (CCR5 ∆32/WT) that is 2.62%. None of the samples were of homozygous genotype (CCR5 ∆32/∆32). Conclusion: The CCR5- ∆32 mutation is a well-studied model of natural selection affecting humans. This mutation is known to occur in the northern Europe and western Asia with higher frequencies. The current study concludes that prevalence of heterozygous CCR5 delta 32 (∆32) mutation is extremely rare in India, also the present clinicians didn’t come across any homozygous case, yet there is need to study larger population to allow statistical comparisons.